Diversity and coherence: historical layers of current civic engagement in Germany - Evers, Adalbert (Voluntas, 2019)
In Germany, like in other countries, the notions of volunteering and civic action altogether describe a wide diversity of activities. Often, this wide spectre is put together under ‘civic engagement’, reaching from civic action that is sometimes overtly ‘political’ over to engagement as volunteering in areas like sports or culture. Yet in academic contributions that use such a wide concept, nothing much can be found about a convincing differentiation of the diverse forms of engagement that figure under such a wide cover. Is there a clear line separating voluntary and civic action? In line with the introduction to this special issue, the paper takes up these questions by proposing that a proper understanding of differentiations in the wide field of civic engagement calls for a historical approach that gives a key role to discourses and politics. Looking from such a perspective at historical constellations in German history, four decisive historical concepts get sketched. It shows that kinds of differentiation between voluntary and civic action are very much dependent on discourses and politics and not only the repercussions of socio-economic and cultural changes and megatrends. The kind of approach chosen shows as well that older concepts, notions and attitudes do not simply melt away in the light of new ones. The label ‘civic engagement’ appears as an umbrella notion in front of a diversity of forms and understandings of engagement. Understanding this diversity calls for tracing the historical roots, notably the ordering imaginaries and strategies wherein these forms and understandings took shape and function today.
Gesehen am 08.07.2019